Health service 'input' and mortality 'output' in developed countries. Issue 3 (September 1978) - Cochrane, A L; St Leger, A S; Moore, F
Abstract : The relationship between age-specific mortality rates and some indices of health facilities and some environmental and dietary factors has been studied in 18 developed couuntries. The indices of health care are not negatively associated with mortality, and there is a marked positive association between the prevalence of doctors and mortality in the younger age groups. No explanation of this doctor anomaly has so far been found. Gross national product per head is the principal variable which shows a consistently strong negative association with mortality.